Non-replaced Mandibular First Molars and Temporomandibular Joint Dysfunction - Gupta, SK; Pratibha, PK; Bhat, KM; Mutalik, S; Guddattu, V (Nepal Journal of Medical Sciences, 2014)
Background: Mandibular first molars serve as key teeth of occlusion. Non replacement of these teeth may affect stability of the dentition and have long term effects on the Temperomandibular joint. The purpose of this study was to observe the association between nonreplaced mandibular molars and temporomandibular joint dysfunction (TMD). Methods: A total of 174 patients, both male and female with missing mandibular first molars, were included in the study. The changes due to non-replacement of mandibular molars were observed clinically. Temporomandibular joint (TMJ) was examined for clinical and radiographic changes. Intra oral findings were correlated with TMJ findings. Results: Supra eruption of opposing maxillary molars and drift of adjacent teeth had a significant association with asymptomatic clicking of the TMJ. Further, patients with deep bite had radiographic findings of condylar flattening. Clicking of the TMJ was a frequent finding in patients with longer duration of molar loss. Conclusion: Missing molars not only have periodontal implications but also far reaching effects on the condylar health of the associated TMJ. Nepal Journal of Medical Sciences | Volume 03 | Number 01 | January-June 2014 | Page 57-62 DOI: http://dx.doi.org/10.3126/njms.v3i1.10360